LEGAL VALIDITY OF NOTARIAL DEEDS SIGNED WITH ELECTRONIC SIGNATURE: (Comparative Study between Indonesian Law and Australian Law) - Wanda Fabiola Emeralda Girsang; Kurniawan Kurniawan; Lalu Muhammad Hayyanul Haq (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
Currently, the profession of Notary holds significant importance in the economic landscape of Indonesia. However, there is a lack of legislation that enables Notaries to execute their duties by creating electronically signable deeds. In Indonesia, an authentic deed prepared by a Notary necessitates physical presence and cannot be executed electronically. This research seeks to identify the legal validity of notarial deeds signed with Electronic Signatures, particularly in Indonesia and New South Wales, Australia. The study aims to understand the regulatory frameworks, examine the nature of Electronic Signatures, and evaluate the implications for contract law in both jurisdictions. Utilizing a Normative Research approach, this study employs the Statute, Conceptual, and Comparative Approaches. Primary legal materials include relevant Indonesian and Australian laws, while secondary and tertiary legal materials provide additional context. A literature review involving books, e-journals, and internet sources contributes to the analysis. The research reveals a gap in explicit regulations governing electronically signed deeds in both Australia and Indonesia. Despite practical application in public contracts, especially in business collaborations, concerns about vulnerability to forgery persist. The absence of clear regulations necessitates a physical appearance before a notary for authentic deeds. The study concludes that regulatory models addressing protection, implementation, and supervision of electronically signed deeds should be explored collaboratively by the Government and the House of Representatives in Indonesia.